2011
DOI: 10.1182/blood-2011-05-352971
|View full text |Cite
|
Sign up to set email alerts
|

Elevated plasma glucosylsphingosine in Gaucher disease: relation to phenotype, storage cell markers, and therapeutic response

Abstract: IntroductionGaucher disease, a relatively common recessively inherited lysosomal storage disorder, is caused by a deficiency in the enzyme glucocerebrosidase, encoded by the GBA gene. 1 Deficient enzymatic activity of glucocerebrosidase results in the lysosomal accumulation of its substrate glucosylceramide, most prominently in macrophages. Three variants of Gaucher disease are generally distinguished based on the absence (type 1) or presence of central nervous system involvement 1 (types 2 and 3). In the much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
233
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 238 publications
(259 citation statements)
references
References 52 publications
15
233
0
3
Order By: Relevance
“…Given the role of osteoblast dysfunction in the development of osteopenia of GD1, (11,17,18) it will be important to determine whether alternative treatments with small molecule substrate reduction therapy, whose volume of distribution includes cells other than macrophages, result in an enhanced therapeutic effect. In a pooled retrospective study of GD1 patients, substrate reduction therapy with miglustat appeared to modestly increase bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the role of osteoblast dysfunction in the development of osteopenia of GD1, (11,17,18) it will be important to determine whether alternative treatments with small molecule substrate reduction therapy, whose volume of distribution includes cells other than macrophages, result in an enhanced therapeutic effect. In a pooled retrospective study of GD1 patients, substrate reduction therapy with miglustat appeared to modestly increase bone mineral density.…”
Section: Discussionmentioning
confidence: 99%
“…(12,13) Although osteopenia in GD is commonly attributed to increased osteoclastic bone resorption, (14) it is more likely related to impaired osteoblast function (15,16) associated with accumulating lipids. (17,18) Importantly, it is not known whether osteopenia in GD1 increases the risk of fractures as it does in postmenopausal women. (19) Imiglucerase therapy improves bone mass and bone mineral density (12,13,(20)(21)(22)(23) and studies have shown an apparent decrease in reports of bone pain and bone crises.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of this chitinase and chemokine in plasma of GD1 patients is, therefore, used as biomarker to assess body burden of Gaucher cells. The glycosphingoid base (lyso-GSL) of the primary storage lipid GlcCer, glucosylsphingosine (GlcSph), is also markedly increased in plasma of symptomatic GD1 patients and its potential as a biomarker has been increasingly recognized [4][5][6]. Accumulation of GlcSph in GD patients was firstly documented in brain of neuronopathic patients several decades ago [7,8].…”
Section: Highlightsmentioning
confidence: 99%
“…A sensitive method for accurate quantification of GlcSph in biological samples, employing LC-MS/MS and an isotope-labelled internal standard, has meanwhile been developed [5]. Recent studies suggest that plasma GlcSph levels correlate with disease severity in GD1 patients [4] and its monitoring is considered useful to evaluate disease status and efficacy of therapeutic intervention. In male Fabry patients with classic disease manifestations a reminiscent phenomenon occurs.…”
Section: Highlightsmentioning
confidence: 99%
“…9,10 We previously detected GCerase activity in normal erythroblasts but not in circulating RBCs. 11 High lipid levels have been frequently reported in the plasma and RBCs of GD patients, [22][23][24][25] which raises the possibility that the RBCs are overloaded with lipids due to the passive incorporation of GlcCer and/or that the erythroid progenitors are primarily affected. To evaluate the alterations in the erythroid progenitors, we performed in vitro experiments to study the erythroid differentiation from peripheral blood samples from GD type 1 patients.…”
Section: Introductionmentioning
confidence: 99%